Benedict XVI’s Participation in the Ecumenical Dialogue with the Orthodox Church - Warzeszak, Józef (Teologia w Polsce, 2020)
The author of this article presents the involvement of Benedict XVI in the ecumenical dialogue with the Eastern Orthodox Church as a whole based on speeches, declarations and homilies delivered to representatives of this Church. Undoubtedly, it is significant. As a pope, he encouraged this dialogue by his authority, fraternal treatment filled with friendship and love, meetings, communal prayer and teaching. He overcame various difficulties and contributing to the progress of this dialogue. He emphasized joint theological research, because without the unity of faith there is no complete and visible unity. As always – as the theologian and as the Prefect of the Congregation for the Doctrine of the Faith – he taught that common celebration of the Eucharist could take place only in full unity: when will it happen? It is God’s gift for which we have to pray and work at the same time: to evangelize together, to resist ideologies hostile to Christianity and humanity, to care for peace and justice among Christians and followers of other religions, and to cooperate in charitable work for the poor, the sick and the needy.